Raspberry-like hollow carbon nanospheres with enhanced matrix-free peptide detection profiles - Liu, T.; Qu, L.; Qian, K.; Liu, J.; Zhang, Q.; Liu, Lihong; Liu, S. (2015)
Raspberry-like hollow carbon spheres have been successfully obtained by the extension of Stöber's method. The raspberry-like hollow carbon spheres demonstrate a much better performance than hollow carbon spheres with a smooth surface in matrix-free peptide detection due to their high capability to capture the small peptide molecule.